1979
DOI: 10.1111/j.1600-0447.1979.tb06948.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that depression rating scales primarily measure a social undesirability response set

Abstract: Many popular methods of measuring depression have not been adequately validated for discriminant validity from social desirability. In a study of 26 patients, 14 with secondary depression, and 12 nondepressives, it was shown that the commonly used Beck Depression Inventory and MMPI Depression scale and the Carroll self-administering version of the Hamilton scales correlate as highly with social undesirability as with each other. Social desirability ratings of item alternatives on the Beck and Hamilton scales b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…It may be tempting to reduce our results to the differences in means among the BDI subgroups reported in Table I, and to equate our findings with extant results. Previously, Beck (1972), Tanaka-Matsumi and Kameoka (1986), and Langevin and Stancer (1979) reported a negative association between the BDI and social desirability. The present study extends these findings by localizing social desirability and denial within an identifiable subgroup, most of whom were extremely low scorers on the BDI, as was suggested by Kendall et al (1987).…”
Section: $-mentioning
confidence: 96%
“…It may be tempting to reduce our results to the differences in means among the BDI subgroups reported in Table I, and to equate our findings with extant results. Previously, Beck (1972), Tanaka-Matsumi and Kameoka (1986), and Langevin and Stancer (1979) reported a negative association between the BDI and social desirability. The present study extends these findings by localizing social desirability and denial within an identifiable subgroup, most of whom were extremely low scorers on the BDI, as was suggested by Kendall et al (1987).…”
Section: $-mentioning
confidence: 96%
“…Langevin and Stancer [22] hypothesized that, because the low self-esteem of depressed patients implies attributing socially undesirable qualities to the self, depression scales might in fact mainly measure social undesirability. In a small study correlations of the Edwards Social Desirability Scale with the Beck Depression Inventory, Carroll Self-Rating Depression Scale, and MMPI Depression Scale were between 0.8 and 0.9.…”
Section: Sources Of Discrepancymentioning
confidence: 99%
“…The score on the BDI represents a measure for depression (26) and low self-esteem (27). Taylor and Falconer (14) found a trend for right-sided temporal lobe surgery to be more frequent in their patient group with neurosis and depression, and Naylor et al (21) reported a higher frequency of right-sided surgery in patients with postoperative depression.…”
Section: Anatomical Considerationsmentioning
confidence: 98%